A microfluidic model of human brain (μHuB) for assessment of blood brain barrier. Issue 2 (13th January 2019) - Brown, Tyler D.; Nowak, Maksymilian; Bayles, Alexandra V.; Prabhakarpandian, Balabhaskar; Karande, Pankaj; Lahann, Joerg; Helgeson, Matthew E.; Mitragotri, Samir
Abstract: Microfluidic cellular models, commonly referred to as "organs‐on‐chips, " continue to advance the field of bioengineering via the development of accurate and higher throughput models, captivating the essence of living human organs. This class of models can mimic key in vivo features, including shear stresses and cellular architectures, in ways that cannot be realized by traditional two‐dimensional in vitro models. Despite such progress, current organ‐on‐a‐chip models are often overly complex, require highly specialized setups and equipment, and lack the ability to easily ascertain temporal and spatial differences in the transport kinetics of compounds translocating across cellular barriers. To address this challenge, we report the development of a three‐dimensional human blood brain barrier (BBB) microfluidic model (μHuB) using human cerebral microvascular endothelial cells (hCMEC/D3) and primary human astrocytes within a commercially available microfluidic platform. Within μHuB, hCMEC/D3 monolayers withstood physiologically relevant shear stresses (2.73 dyn/cm 2 ) over a period of 24 hr and formed a complete inner lumen, resembling in vivo blood capillaries. Monolayers within μHuB expressed phenotypical tight junction markers (Claudin‐5 and ZO‐1), which increased expression after the presence of hemodynamic‐like shear stress. Negligible cell injury was observed when the monolayers were cultured statically, conditioned to shear stress, and subjected to nonfluorescent dextran (70 kDa) transport studies. μHuB experienced size‐selective permeability of 10 and 70 kDa dextrans similar to other BBB models. However, with the ability to probe temporal and spatial evolution of solute distribution, μHuBs possess the ability to capture the true variability in permeability across a cellular monolayer over time and allow for evaluation of the full breadth of permeabilities that would otherwise be lost using traditional end‐point sampling techniques. Overall, the μHuB platform provides a simplified, easy‐to‐use model to further investigate the complexities of the human BBB in real‐time and can be readily adapted to incorporate additional cell types of the neurovascular unit and beyond.